2022
DOI: 10.3390/diagnostics12081879
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Acne Object Detection and Acne Severity Grading Using Smartphone Images and Artificial Intelligence

Abstract: Skin image analysis using artificial intelligence (AI) has recently attracted significant research interest, particularly for analyzing skin images captured by mobile devices. Acne is one of the most common skin conditions with profound effects in severe cases. In this study, we developed an AI system called AcneDet for automatic acne object detection and acne severity grading using facial images captured by smartphones. AcneDet includes two models for two tasks: (1) a Faster R-CNN-based deep learning model fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Similarly, image-based analysis is another prospect to detect face acne, which is possible by comparable severities checks where similar appearances are complex to examine, as shown in Figure 1. To overcome this situation, there is a need to adopt a complex network based on neurons, which consume more resources including computational cost and preservation [8,9]. Whereas the computational cost indicates the powerful graphical processing units that require a high-specification environment for deployment purposes.…”
Section: D-gan: An Automatic Acne Detection Severity and Assessment F...mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, image-based analysis is another prospect to detect face acne, which is possible by comparable severities checks where similar appearances are complex to examine, as shown in Figure 1. To overcome this situation, there is a need to adopt a complex network based on neurons, which consume more resources including computational cost and preservation [8,9]. Whereas the computational cost indicates the powerful graphical processing units that require a high-specification environment for deployment purposes.…”
Section: D-gan: An Automatic Acne Detection Severity and Assessment F...mentioning
confidence: 99%
“…On the other side, there are a few challenging prospects that effects the employment of DNN with other state-of-the-art methods for the better result of acne severity. Generative Adversarial Network (GAN) is associated with generative modeling, which is an unsupervised learning approach based on automation to discover learning and patterns of input values in accordance with the regulations [8,9,10]. In such a way that the model can be used to give output as a new example drawn from the original one.…”
Section: Figure 1 the Current Process Of Acne Detectionmentioning
confidence: 99%
“…Yadav et al [5] identified candidate regions of acne presence on the face based on the HSV color space and then distinguished acne using classifiers trained with SVM or CNN. Rashataprucksa et al [6] and Hyunh et al [7] utilized object detection models such as faster-rcnn [8] and r-fcn [9] for acne detection. Min et al [10] employed a dual encoder based on CNN and Transformer to detect face acne.…”
Section: Introductionmentioning
confidence: 99%
“…Dermatology has become a hot topic in AI due to the visible clinical manifestations of skin diseases. In recent years, machine learning (ML) has played a large role in detecting and grading acne severity, distinguishing atopic dermatitis, classifying skin cancer, and detecting monkeypox with a level of accuracy comparable to a dermatologist 18–21 . However, the prospect of AI in deep skin fungal infection has not been investigated thus far.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, machine learning (ML) has played a large role in detecting and grading acne severity, distinguishing atopic dermatitis, classifying skin cancer, and detecting monkeypox with a level of accuracy comparable to a dermatologist. [18][19][20][21] However, the prospect of AI in deep skin fungal infection has not been investigated thus far. Therefore, it is A study was included in the study when it met all following criteria: (1) a study that showed skin lesion images for talaromycosis or cryptococcosis; (2) cases were diagnosed using the gold standard; and (3) the images were clearly visible.…”
mentioning
confidence: 99%